Homeschooling and controversies: from identity to plurality – the drama of socialization (Práxis Educativa, 2020)
To analyze the problem of home education highlighting the main points present in the literature, however, bringing to light, originally, the binomial identity-plurality is the objective of this work. The theme has been studied from several perspectives: legal and historical, economic and ideological, marketing, comparative law, pedagogical theory, as individual right to freedom, motivation of choices, etc. The guiding questions are: What controversies suggest home education when considering the operationalization of the school curriculum in households? What risks does home education present for the identity-plurality binomial in the socialization process for the formation of citizenship? This paper, therefore, is a qualitative research based on primary and documentary sources, websites, as well as literature. The results indicate that screening and classification will occur in defense of the “good socialization” advocated by homeschoolers and if the state does not monitor, a completely plausible possibility, the risks of formation of family social bubbles are imminent.Keywords: Homeschooling. Identity. Plurality.